Produtos biológicos e químico no manejo de Spodoptera eridania (Cramer) (Lepidoptera: Noctuidae) na cultura da soja - Bruno Mateus Ribeiro Dias (2021)
The Spodoptera eridania species considered a pest of growing importance of soybeans, due to its damage during the crop cycle. Chemical insecticides are used to control them, which can lead to the selection of harmful ones and the reduction of harmful ones. Microbiological insecticides may be efficient in controlling this insect pest. The objective of this work was to evaluate the efficiency of microgenic insecticides, based on entomopathogenic and chemical fungi, on eridania in soybean. The experiment was carried out in the municipality of Chapadão do Sul-MS, on the Campus of the Federal University of Mato Grosso do Sul. The experimental design was in randomized blocks, consisting of four blocks and six treatments, totaling 24 plots. The treatments used were: T1- Control, T2- 1.0 kg ha-1 of Chlorpyrifos insecticide, T3- 225 g ha-1 of Beauveria bassiana, T4- 0.5 L ha-1 of Metarhizium anisopliae, T5- 450 g ha-1 of B. bassiana and T6- 1.0 L ha-1 of M. anisopliae. Treatments were applied 1 when observed, being linear pellets/meter, in a single dose. At 14 treatments performed after application a counting the number of 7 days after the use of live plots. At the time of harvest, the phytotechnical parameters of the crop were estimated. The data obtained from live caterpillars and phytotechnical data were selected for analysis of variance (ANOVA), with the data obtained being the comparison between the averages of the treatments performed by the Tukey test (p ≤ 05). The performance reduction and efficiency reduction work of Henderson &5 was carried out. The application of M. anisopliae in the dosages of 1 L ha1 and 0.5 L ha-1 and of B. bassiana in the combinations of 450 g ha-1 provided, respectively, 78.1%, 66% and 64% in the harnessing control of S. eridania caterpillars. The Chlorpyrifos insecticide achieved an efficiency of 49.0%. Regarding the parameters, portable plant height, number of linear plants, number of grains per plant, number of grains per pod and grain mass, no significant differences were observed. A statistically superior superior productivity for the biological treatments in relation to the chemical and the control, except for the treatment with B. bassiana in the comparison of 225 g ha-1.